Three Faces of Civil Society Activism in Nepal - Basnet, Chudamani (New Angle: Nepal Journal of Social Science and Public Policy, 2012)
This article consists of an ethnographically informed analysis of the ‘logic’ guiding civil society activism in Nepal at three distinct points in its recent history. The paper details these ‘logics’ (‘service logic’ (1990 2000), a ‘peace logic’ (2001-2004) and a more radical and egalitarian logic (2005-2006)) and then relates the corresponding types of civil society (civil society I, civil society II and civil society III, respectively) to broader political developments in the country. It is argued that the changes in the logic underpinning civil society activism can clearly be attributed to the changing patterns of macro power configurations and to distinct challenges faced by the urban literate class over the previous two decades.